The competence and Professional practice of supervisor in Latvia: the results of pilotsurvey - Mārtinsone, Kristīne; Mihailova, Sandra; Mihailovs, Ivans Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Supervision today is gradually becoming a component or compulsory part of professional practice un studies, especially in areas where the focus is a person, psychology, art-therapies, social work, psychoterapy, as well as civil service, pedagogy etc.Supervision is process, where is being reflected on the challenges facing both the client or patient and of the relationship that occurs between staff and clients or patients, both for the specialist are able to comply with the requirements of professional, ethical, as well as the difficulties in dealing with clients patients.Aim of the paper is to present the results of pilot stud (survey)y, how supervision of our country (Latvia) understand the various professions and how supervision in our country is being implemented supervision’s practice in various professional fields.The article highlights the issue of supervisor education problems in Latvia, analyzing the current situation and the legal framework, which is a prerequisite for quality supervision system in the country.